Tracing back trauma: the legacy of slavery in contemporary Afro-Brazilian literature by women - Williams, C (Routledge, 2017)
Although there are many, mostly male, contemporary writers in Brazil whose narratives of urban violence and social inequality implicitly reflect the impact and legacy of slavery on contemporary society, it is interesting that this shameful period, and shockingly brutal events which seem to prove wrong the myths of gentle colonization and harmonious racial democracy, should be chosen as subject matter by four women writers. While very different novels, Adriana Lisboa’s Os Fios da Memória [The Threads of Memory] (1999), Conceição Evaristo's Ponciá Vicêncio (2003), Ana Maria Gonçalves's Um Defeito de Cor [A Defect in Colour] (2006) and Tatiana Salem Levy's Paraíso [Paradise] (2014) all deal frankly with the horrors of slavery and its aftermaths from the point of view of the most vulnerable member of colonial society: the enslaved African woman. This article analyses the ways in which these writers claim justice for their characters and remind readers that those excluded from official histories had names, faces and voices.